2020
DOI: 10.1111/1744-7917.12840
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein–protein interactions between rice viruses and vector insects

Abstract: Planthoppers are the most notorious rice pests, because they transmit various rice viruses in a persistent-propagative manner. Protein-protein interactions (PPIs) between virus and vector are crucial for virus transmission by vector insects. However, the number of known PPIs for pairs of rice viruses and planthoppers is restricted by low throughput research methods. In this study, we applied DeNovo, a virus-host sequencebased PPI predictor, to predict potential PPIs at a genome-wide scale between three plantho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Affinity through the Importin β-Binding Domain. In our previous work, importin α2 was found to interact in vitro with RSV NP (26,27). Here, we confirmed the contact of the two proteins in vivo through coimmunoprecipitation (Co-IP) assays using the monoclonal anti-NP antibody to pull down the complex of importin α2 and NP from the total protein of viruliferous planthoppers (Fig.…”
Section: Importin α2 Binds Viral Nucleocapsid Protein With a Relatively Highsupporting
confidence: 83%
“…Affinity through the Importin β-Binding Domain. In our previous work, importin α2 was found to interact in vitro with RSV NP (26,27). Here, we confirmed the contact of the two proteins in vivo through coimmunoprecipitation (Co-IP) assays using the monoclonal anti-NP antibody to pull down the complex of importin α2 and NP from the total protein of viruliferous planthoppers (Fig.…”
Section: Importin α2 Binds Viral Nucleocapsid Protein With a Relatively Highsupporting
confidence: 83%
“…In our recent work, we predicted protein-protein interactions between five rice viruses (RSV, rice black-streaked dwarf virus, rice grassy stunt virus, rice ragged stunt virus, and southern rice black-streaked dwarf virus) and their respective vector insects ( L. striatellus , Nilaparvata lugens , and Sogatella furcifera ) on a genome-wide scale using the DeNovo method [ 18 ]. Ago2 and Translin were predicted to be able to bind NS2 and RdRp of RSV, respectively, and the in vitro pulldown assay showed that translin bound fragment 2 from amino acid (aa) 482 to 1051 of RdRp [ 18 ]. To further verify these protein-protein interactions, NS2 and fragment 2 of RdRp (RdRp2) were recombinantly expressed with His-tags.…”
Section: Resultsmentioning
confidence: 99%
“…NS3 regulates the rice miRNA pathway by interacting with double-stranded RNA-binding protein 1 (OsDRB1), which is necessary for the formation of mature miRNAs [ 39 ]. However, based on our bioinformatic prediction of protein-protein interactions between rice viruses and their vector insects [ 18 ], it is unlikely that NS3 binds Ago or Dicer proteins of the planthoppers. As RNAi suppressors, NS2 and NS3 function differently both in vector insects and in host plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sugar transporter 6, which has been proved to be helpful for RSV entry into the midgut cells of planthoppers ( 13 ), no other midgut cell membrane proteins have been identified as possible receptors of RSV. In our recent work, we predicted protein-protein interactions between five rice viruses [RSV, southern rice black-streaked dwarf virus (SRBSDV), rice ragged stunt virus (RRSV), rice black-streaked dwarf virus (RBSDV), and rice grassy stunt virus (RGSV)] and their respective vector insects ( L. striatellus , Nilaparvata lugens , and Sogatella furcifera ) on a genome-wide scale using the de novo method and provided a list of potential conserved vector proteins that are essential for the transmission of rice viruses ( 14 ). Flotillin 2 is one of these conserved vector proteins, and the interaction between the RSV NP and flotillin 2 of small brown planthopper was verified in vitro ( 14 ).…”
Section: Introductionmentioning
confidence: 99%